PENGARUH PROGRESSIVE MUSCLE RELAXATION TERHADAP PERUBAHAN INSOMNIA DAN KEMAMPUAN RELAKSASI PADA LANSIA DI PANTI SOSIAL TRESNA WHERDA KABUPATEN BUNGO - Mareta Akhriansyah; budi anna keliat; Feri Fernandes (Jurnal Kesehatan Medika Saintika, 2019)
Abstrak Memasuki usia tua bisa mengalamikemunduran fisik seperti kulit mengendur, gerakan lambat dan postur tubuh yang tidak proforsional sehingga mempengaruhi psikologis pada lansia. Gangguan pemenuhan kebutuhan tidur merupakan dampak masalah psikologis yang sering muncul pada lansia.Sekitar 80% dari klien depresi dan 90 % dari klien tersebut insomnia. Penelitian ini bertujuan untuk mengetahui pengaruh terapi Progressive Muscle Relaxation (PMR) terhadap insomnia dan kemampuan relaksasi pada lansia di PSTW. Desain penelitian Quasi Experimental Pre-Post Test With Control Grup. Pengambilan sampel dilakukkan dengan teknik simple random samplingdimana 84 orang lansia, 42 orang lansia kelompok intervensi yang diberikan terapi generalis dan PMR dan 42 orang lansia kelompok kontrol yang hanya diberikan terapi generalis. Hasil penelitian ditemukan penurunan insomnia dengan nilai (p value< 0,05). Study ini menunjukkan ada perbedaan yang bermakna setelah diberikan terapi PMR pada kelompok intervensi. Sedangkan kemampuan relaksasi pada lansia yang mendapatkan terapi generalis dan PMR meningkat secara bermakna (p value< 0,05). Terapi generalis dan PMR direkomendasikan sebagai terapi keperawatan lanjutan dalam merawat lansia dengan insomnia. Kata Kunci : Insomnia, Lansia, Progressive Muscle Relaxation   THE INFLUENCE OF PROGRESSIVE MUSCLE RELAXATION THERAPHY FOR INSOMN BEHAVIOR CHANGE AND RELAXATION SKILL OF ELDERLY POPULATION IN SOCIAL RESIDENCIAL ELDERLY HOSTELS (TRESNA WERDHA) IN BUNGO REGENCY                                                      Mareta Akhriansyah1, Budi Anna Keliat2, Feri Fernandes3 1Mareta Akhriansyah, Master of Nursing Student, Faculty of Nursing, Andalas University, Padang, West Sumatra.email:mareta_ners@yahoo.com, 085268840840 2Budi Anna Keliat, Department of Scientific Specificity of Soul Nursing, Faculty of Nursing, University of Indonesia, FIK UI Depok.E-mail: budianna_kelia@yahoo.com,08128100821 3Feri Fernandes, Master of Nursing Lecturer, Faculty of Nursing, Andalas University, Padang, West Sumatra.Email :ferifernandes13@yahoo.co.id, 081363133500 Abstract In the Old age of people, they are possible to feel any decadency of physical effect such as sagging of skin, slowly of movement and unproportional of body posture it could be influence their psychologic.  Insomn Behavior is an impact of psychologic which is appear in elderly population. Is ablout 80 % of patient are in depression condition and 90% of patients are in insomn behavior. This research aimed to determine the influence of Progressive Muscle Relaxation (PMR) theraphy for insomn behavior of elderly in Social Residencial/ Elderly Hostels. The research was using Quasi-experimental method with pre test-post test with control group. Techniq sampling was using  simple random sampling where 84 elderly as respondens, 42 respondens are grouping by intervention group were given general therapy and PMR and the other 42 respondens are grouping by control group were only given a general therapy. The result of this research founded that PMR theraphy can reduce insomn behavior and with value (p value < 0.05). This researchs were indicated a good difference after they’ve got PMR theraphy in Intervention Group.  While relaxation skill in elderly population which is getting general theraphy and PMR are increasing with good value (p value < 0.05). General therapy and PMR are recommended as a treatment for advanced nursing therapy of elderly with insomn behavior. Keywords   : Insomn Behavior , Elderly Population, Progressive Muscle Relaxtation